Pengolahan Limbah Cair Laundry Menggunakan Serat Gambas (Luffa Acutangula) Dan Arang Aktif Untuk Menurunkan Kadar Fosfat - Monika, Diah; Narto, Narto; Amri, Choirul (Jurnal Kesehatan Lingkungan Mapaccing, 2026)
The need for the laundry industry in Indonesia is increasing along with the increase in public demand. However, laundry waste contains phosphate compounds which, if not treated properly, will threaten the sustainability of the ecosystem and human health. This study aims to treat laundry waste by adsorption filtration using gambas fiber and activated charcoal. Methods:This type of research is an experimental pre post test without control design with a media thickness of 100 cm consisting of 3 different adsorbent media thickness composition formulas namely 25:75 (F1), 50:50 (F2), 75:25 (F3), each repeated 3 times. The results of the analysis showed a significant decrease in waste phosphate levels of 4.03 mg/l, 3.43 mg/l and 2.63 mg/l, the percentage decrease was 79.90%, 67.98%, and 52.12%. Conclusion: There is a significant difference between the thickness variations of the three groups of gambas and charcoal media on the reduction of laundry phosphate levels in this study.